Platelet Membrane Biomimetic Nanoparticles Combined With UTMD to Improve the Stability of Atherosclerotic Plaques - Zhou, Jia; Niu, Chengcheng; Huang, Biying; Chen, Sijie; Yu, Caigui; Cao, Sheng; Pei, Wenjing; Guo, Ruiqiang (Frontiers in Chemistry, 2022)
Although research on the treatment of atherosclerosis has progressed recently, challenges remain in developing more effective, safer and transformative strategies for the treatment of atherosclerosis. Nanomaterials have recently played a unique role in many fields, including atherosclerosis treatment. Platelets are common component in the blood. Due to their inherent properties, platelets can target and adhere to atherosclerotic plaques. Ultrasound-targeted microbubble destruction (UTMD) shows great prospects in promoting the efficiency of drug delivery in treating solid tumors. In this study, we explored the possibility that UTMD assists platelet biomimetic rapamycin (RAP)-loaded poly(lactic-co-glycolic acid)(PLGA) nanoparticles (RAP@PLT NPs) in the treatment of atherosclerosis. The biomimetic nano-formulations exhibit better targeting ability to plaques when administered in vivo. Targeted destruction of SonovueTM in the aortic area further improved the efficiency of targeting plaques. Moreover, the progression of atherosclerotic plaques was inhibited, and the stability of plaques was improved. Together, our study established a novel strategy for targeted delivery of nanoparticles in atherosclerotic plaques, by combining the advantages of the ultrasonic cavitation effect and biomimicking nanoparticles in drug delivery.